Association between circulatory immune cell to high-density lipoprotein cholesterol ratios and testosterone level in adult men: findings from NHANES 2011–2016 - Yangyang Mei; Bo Zhang; Yiming Chen; Renfang Xu; Dong Xue; Qianfeng Zhuang; Xingliang Feng (BMC Endocrine Disorders)
Abstract Background Testosterone is essential for male health, and its decline is closely associated with inflammation and lipid metabolism. The ratio of circulatory immune cells to high-density lipoprotein cholesterol (HDL-C) can comprehensively reflect these underlying pathophysiological mechanisms, including the neutrophil-to-HDL-C (NHR), platelet-to-HDL-C (PHR), monocyte-to-HDL-C (MHR), and lymphocyte-to-HDL-C (LHR). This study is the first to comprehensively assess the relationship between these ratios and male testosterone levels, as well as their ability to predict testosterone deficiency (TD).  Methods The study data were derived from the NHANES 2011–2016 cycles, including adult males who with data on the aforementioned indicators. Multivariable linear regression and logistic regression analyses were performed to assess the impact of these ratios on total testosterone levels and the risk of TD, respectively. Smoothed curve fitting was used to determine potential nonlinear relationships. Additionally, ROC analysis was conducted to compare the predictive ability of NHR, PHR, MHR, and LHR for TD. Finally, subgroup analysis was performed to confirm the stability of the results.  Results A total of 6,079 participants were included in the study, with 1,680 participants having TD. In the fully adjusted models, log-transformed NHR, PHR, MHR, and LHR were all linearly negatively associated with total testosterone levels and linearly positively associated with the risk of TD. Specifically, for NHR, the corresponding beta and odds ratio (OR) were (β = -66.58, 95% CI: -78.08, -55.08, P < 0.0001) and (OR = 2.21, 95% CI: 1.76, 2.77, P < 0.0001), respectively. Similarly, for PHR, the OR for the risk of TD was 2.24 (95% CI: 1.64, 3.05, P < 0.0001), for MHR, the OR was 1.82 (95% CI: 1.42, 2.32, P < 0.0001), and for LHR, the OR was 2.11 (95% CI: 1.63, 2.74, P < 0.0001), indicating significant positive associations with TD risk. Additionally, ROC analysis indicated that NHR had the best predictive ability for TD among the ratios, with the highest AUC of 0.640 (95% CI: 0.625–0.655) and consistent results across subgroups.  Conclusion Our results suggest that log-transformed NHR, PHR, MHR, and LHR are positively associated with the risk of TD, with NHR being an effective predictor of TD. These findings highlight the potential of NHR to serve as an accessible supplementary biomarker for identifying men who may be at higher risk of TD, supporting early risk stratification and guiding further evaluation where appropriate. However, further prospective cohort studies are essential to validate our findings.